Soluble B7-CD28 Family Inhibitory Immune Checkpoint Proteins and Anti-Cancer Immunotherapy - Khan, Muhammad; Arooj, Sumbal; Wang, Hua (Frontiers in Immunology, 2021)
Co-inhibitory B7-CD28 family member proteins negatively regulate T cell responses and are extensively involved in tumor immune evasion. Blockade of classical CTLA-4 (cytotoxic T lymphocyte-associated antigen-4) and PD-1 (programmed cell death protein-1) checkpoint pathways have become the cornerstone of anti-cancer immunotherapy. New inhibitory checkpoint proteins such as B7-H3, B7-H4, and BTLA (B and T lymphocyte attenuator) are being discovered and investigated for their potential in anti-cancer immunotherapy. In addition, soluble forms of these molecules also exist in sera of healthy individuals and elevated levels are found in chronic infections, autoimmune diseases, and cancers. Soluble forms are generated by proteolytic shedding or alternative splicing. Elevated circulating levels of these inhibitory soluble checkpoint molecules in cancer have been correlated with advance stage, metastatic status, and prognosis which underscore their broader involvement in immune regulation. In addition to their potential as biomarker, understanding their mechanism of production, biological activity, and pathological interactions may also pave the way for their clinical use as a therapeutic target. Here we review these aspects of soluble checkpoint molecules and elucidate on their potential for anti-cancer immunotherapy.